A gestão camponesa das águas: o caso do assentamento Che Guevara, Ocara, CE - Cordeiro, Danielle Leite (2013)
The waters of small-size reservoirs spread in the rural areas of Northeastern Brazil have served entire communities. Charged with the responsibility to manage ‘scarcity’, these communities have created their own mechanisms of use and management of wateraccording to the satisfaction of their “livelihoods”. Water ‘scarcity’ in the semiarid region is a result, on one side, of the unequal forms of private use and ownership of this resource, which have historically subjected entire populations to the effects of climate conditions. The other aspect is the expression of struggle for ownership, control, use and broad access to water. Taking these in consideration, this research has the aim of analyzing the water resource management carried out by peasant families of the Settlement Project São José II in the municipality of Ocara, Ceará State, Brazil. A fieldwork research wasconducted with the settled families featuring semi-structured interviews, questionnaires, workshops, and observations of their practices in order to understand their realities. Interviews have also been conducted with dwellers of neighboring communities, representatives of associations and labor unions, and also of Brazil’s Landless Workers Movement (MST) and the Pastoral Commission of Land (CPT), who have been directly and indirectly connected to the settlers. The collective trajectory of these families in the struggle for land forged the necessary conditions for crafting their own systems of water regulation which initially used the resources exclusively available in their territory. Subsequently, in the attempt of increasing water availability, their struggle to expand their rights secured the construction of cisterns, which associated with reservoirs and natural ponds revealed itself as one of the settlement’s major sources of water supply.Water ‘scarcity’ water isn’t seen only in terms of quantity, but essentially in terms of quality. Their attempt to manage water quality generated harmonic relations with nature. The water resource management opened way for necessary territorial changes for developing productive systems that diversified and expanded the settled families’ income and thus created a prosperous environment to the conception of the peasant “lifestyle”.